An Effective Approach for Analyzing “Prefinished” Genomic Sequence Data - Kuehl, Peter M.; Weisemann, Jane M.; Touchman, Jeffrey W.; Green, Eric D.; Boguski, Mark S.

(untitled) (Genome Research, 1999)
Ongoing efforts to sequence the human genome are already generating large amounts of data, with substantial increases anticipated over the next few years. In most cases, a shotgun sequencing strategy is being used, which rapidly yields most of the primary sequence in incompletely assembled sequence contigs (“prefinished” sequence) and more slowly produces the final, completely assembled sequence (“finished” sequence). Thus, in general, prefinished sequence is produced in excess of finished sequence, and this trend is certain to continue and even accelerate over the next few years. Even at a prefinished stage, genomic sequence represents a rich source of important biological information that is of great interest to many investigators. However, analyzing such data is a challenging and daunting task, both because of its sheer volume and because it can change on a day-by-day basis. To facilitate the discovery and characterization of genes and other important elements within prefinished sequence, we have developed an analytical strategy and system that uses readily available software tools in new combinations. Implementation of this strategy for the analysis of prefinished sequence data from human chromosome 7 has demonstrated that this is a convenient, inexpensive, and extensible solution to the problem of analyzing the large amounts of preliminary data being produced by large-scale sequencing efforts. Our approach is accessible to any investigator who wishes to assimilate additional information about particular sequence data en route to developing richer annotations of a finished sequence.[Our software system is available via an extensive web supplement to this article at http://www.ncbi.nlm.nih.gov/Kuehl/prefinished.]